Morphometric Characteristics Of Merawangarab Chicken Based On Multivariate Analysis and Multiple Regression - Sri Darwati; Harini Nurcahya; Hajran Fashbir Pambudi (Journal of Tropical Biodiversity, 2026)
This study aimed to analyze morphometric characteristics of merawangarab chicken using multivariate analysis. Twenty five of merawangarab chicken with 12th weeks age was used. Merawangarab chicken were observed for body weight, body length, wing length, femur length, and tibia length. Data were analyzed using multivariate analysis Principal Component Analysis (PCA) and multiple regression. Body size and body weight were still varied. The first component was mainly associated with body size. Results indicated that the first principal component represented body size index, explaining 93.8% of the total variance. Between variables there was a significant positive correlation (P <0.05) between variables and multiple linear equations Weight = -871 +6.88 Chest Length + 12.49 Tibia Length + 2.58 Femur Length (mm) with R2 = 90.5. Conclusion PC1 controls the variety of variables measured, with a close relationship between variables and still varied and can be used to estimate body weight. Key words: merawangarab chicken, morphometric, multivariate analysis, multiple regression